2019
DOI: 10.1042/bsr20182470
|View full text |Cite
|
Sign up to set email alerts
|

The associations between Toll-like receptor 4 gene polymorphisms and hepatitis C virus infection: a systematic review and meta-analysis

Abstract: Background and objective: The hepatitis C virus (HCV) is able to cause a life-threatening disease relating to lethal hepatocellular carcinoma. Previous, Toll-like receptor polymorphisms were proposed as promising biomarker for HCV-related hepatocellular carcinoma and disease progression. This study aimed to summarize the association of TLR4 polymorphisms and HCV infection through meta-analysis. Methods: We applied a systematic review and meta-analysis performed by using PubMed, EMBASE and Web of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The role of HPV in interfering with hepatocarcinogenesis may be related to the involvement of a Toll-like receptor (TLR). Single-nucleotide polymorphisms in TLR genes may be key markers of an early susceptibility to various cancers, including HCC [ 35 ]. Since they initiate intracellular signaling pathways to induce antiviral mediators, they have been considered as the first line of antiviral immunity [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of HPV in interfering with hepatocarcinogenesis may be related to the involvement of a Toll-like receptor (TLR). Single-nucleotide polymorphisms in TLR genes may be key markers of an early susceptibility to various cancers, including HCC [ 35 ]. Since they initiate intracellular signaling pathways to induce antiviral mediators, they have been considered as the first line of antiviral immunity [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since they initiate intracellular signaling pathways to induce antiviral mediators, they have been considered as the first line of antiviral immunity [ 36 ]. Studies have shown that TLR4 rs4986790 was significantly negatively associated with HCV infection [ 35 ]. Individuals carrying the rs1927911 heterozygous genotype had a significantly reduced risk of HCC [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The participation of a Toll-like receptor (TLR) in HPV's ability to interfere with hepatocarcinogenesis has been hypothesized. Many types of tumors may be predisposed to a person with certain single-nucleotide polymorphisms in the TLR genes (94,95). Under a wide range of oncogenic situations, on the other side, cellular senescence is a critical tumor-suppressive mechanism that causes injured cells to undergo permanent growth arrest, preventing them from proliferating abnormally.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that there are functions relating to RNA stability and regulation, resulting in alteration of protein expression because several translated regions or a part of intron might relate to miRNA [36]. Moreover, previous in silico analysis showed that rs2149356G is able to form miRNA which targets autophagy genes [37]. Therefore, rs1927911 and rs12377632 should be under this circumstance.…”
Section: Figure 3 Forest Plot Of Association Between Two Tlr4 Polymomentioning
confidence: 99%